Diffusing a Research-based Physical Activity Promotion Program for Seniors Into Diverse Communities: CHAMPS III - Anita L. Stewart, PhD; Dawn Gillis, MS; Melanie Grossman, PhD; Martha Castrillo; Leslie Pruitt, PhD; Barbara McLellan, MPH; Nina Sperber, MA (Centers for Disease Control and Prevention, 2006)
Introduction Increasing the physical activity levels of older adults through diffusion of successful research-based programs into community settings is challenging because of differences between research and real-world settings. This project diffused the Community Healthy Activities Model Program for Seniors (CHAMPS) II, an individual-level research-based physical activity promotion program, through three community organizations to reach lower-income and minority (primarily Hispanic or Latino and African American) seniors. Methods Through an academic-community partnership, university staff worked with each organization to adapt the program to be appealing and effective, enable their staff and volunteers to provide the program, increase participants' physical activity, and leave sustainable programs in place. Evaluation was based on methods recommended by the Centers for Disease Control and Prevention. Results The adapted programs, referred to as CHAMPS III, differed from the original program and among organizations. Group-based components and resource guides were included and new features were added; however, individualized components were not offered because of limited resources. A total of 321 people enrolled among three organizations; there was a trend toward increased physical activity at two organizations (an estimated increase of 481 kcal/week [P = .08] and 437 kcal/week [P = .06] expended in physical activity). Evaluation revealed challenges and unexpected community-level benefits. All organizations are continuing efforts to promote physical activity for older adults. Conclusion This project enabled community organizations to implement physical activity promotion programs. The overarching challenge was to retain original program features within each organization's resources yet be sustainable. Although the programs differed from the original research program, they were a catalyst for numerous community-level changes. Our findings can guide similar projects to reach underserved older adults.